Circulating interleukin-18 (IL-18) is a predictor of response to gemcitabine based chemotherapy in patients with pancreatic adenocarcinoma. Issue 4 (April 2017) - Usul Afsar, Çiğdem; Karabulut, Mehmet; Karabulut, Senem; Alis, Halil; Gonenc, Murat; Dagoglu, Nergiz; Serilmez, Murat; Tas, Faruk
Abstract: Background: This study was conducted to investigate the serum levels of interleukin-18 (IL-18) in patients with pancreatic adenocarcinoma (PA) and the relationship with tumor progression and known prognostic parameters. Methods: Thirty-three patients with PA were studied. Serum samples were obtained on first admission before any treatment. Serum IL-18 levels were analyzed using enzyme-linked immunosorbent assay (ELISA). Age- and sex-matched 30 healthy controls were included in the analysis. Results: The median age at diagnosis was 59 years, range 32–84 years; 20 (61%) patients were men and the remaining were women. The median follow-up time was 26.0 weeks (range: 1.0–184.0 weeks). The median overall survival of the whole group was 41.3 ± 8.3 weeks [95% confidence interval (CI) = 25–58 weeks]. The baseline serum IL-18 levels were significantly higher in patients with PA than in the control group (p < 0.001). Serum IL-18 levels were significantly higher in the patients with high erythrocyte sedimentation rate (ESR) and lactate dehydrogenase (LDH) (p = 0.01 and p = 0.05). Moreover, the chemotherapy-(CTx) unresponsive patients had higher serum IL-18 levels compared to CTx-responsive (p = 0.04) subjects. Conversely, serum IL-18 concentration was found to have no prognostic role on survival (p = 0.45). Conclusion: Serum levels of IL-18 can be a good diagnostic and predictive marker; especially for predicting the response to gemcitabine based CTx in patients with PA but it has no prognostic role.